Evaluation of lipid profile and oxidative stress in STZ-induced rats treated with antioxidant vitamin - Almeida, Danielle Ayr Tavares de; Braga, Camila Pereira [UNESP]; Novelli, Ethel Lourenzi Barbosa [UNESP]; Fernandes, Ana Angélica Henrique [UNESP] (Brazilian Archives of Biology and Technology, 2012)
The present study investigated the effect of supplementation of vitamin E on streptozotocin (STZ)-induced diabetic rats by measuring blood glucose, changes in body weight, food and water intake, lipid profile, serum urea and creatinine level, and antioxidant enzyme activity. Male Wistar rats were divided into four groups: control rats (GI); rats receiving vitamin E (GII); STZ-induced diabetic rats (GIII) and STZ-induced diabetic rats treated with vitamin E (GIV). Vitamin E reduced (p<0.05) blood glucose and urea, improved the lipid profile (decreased the serum levels of total cholesterol, LDL cholesterol, VLDL cholesterol and triacylglycerols, and increased HDL cholesterol) and increased total protein in STZ-induced diabetic rats (GIV). Vitamin prevented changes in the activity of SOD and GSH-Px and in the concentration of lipid hydroperoxide. These results suggested that vitamin E improved hyperglycaemia and dyslipidaemia while inhibiting the progression of oxidative stress in STZ-induced diabetic rats.
Keywords: vitamin E; lipid profile; oxidative stress; STZ